Satwa Negeriku: STEM-based encyclopedia as literacy media for elementary student - Mukhsin Alfian; Ika Maryani (JURNAL BIOEDUKATIKA, 2020)
This research aims to develop, measures the feasibility, and implements STEM-based Encyclopedia to train the literacy of elementary school students. This study uses a 4D development model from Thiagarajan. The subjects were students in grades 4, 5, and 6 of the teachers at Muhammadiyah Pepe Elementary School, Yogyakarta. Encyclopedias were tested on students and teachers after proper approval by material experts, linguists, and media experts. Data obtained through questionnaires, interviews, field notes and observations. The validation results show that the Encyclopedia is worth using to support the literacy program. The results of the small group trial received a value of 95 (very good), the large group trial received a score of 92 (very good), and also the good application received a score of 91.5 (very good). Students find encyclopedias very interesting, easy to understand, and increase students' understanding of endangered species in Indonesia. The observations also show the use of STEM-based encyclopedias leading to the realization of competency literacy indicators. The teacher also appreciates that the encyclopedia is suitable to be used as teaching material that supports the literacy program.